Early Childhood Education in Indonesia; A Primary Study on The Beneficiary Family of International Non-Government Organization - Akiko Lahitani; RR. Endah Sulistyaningsih (Asian Social Work Journal, 2020)
This study aimed to examine the prevalence of parental understanding on the Early Childhood Education in the beneficiary family of programs held by the International Non-Government Organization. The research participants were the beneficiary family listed and provided by World Vision Indonesia and Child Fund Indonesia. The research used a quantitative research approach with self-administered survey instruments. The sample used for the present research is the beneficiary of the programmes that had been implemented by INGO, which includes 325 research participants located in Jakarta and Banten. The data collection took place on March 2020 using online media survey, with validity test have been done before the research instruments shared to all the participants. There were nine questions in the survey with nominal data value for every question rated on a 5-point Likert scale and the ratings summed into items corresponding to early childhood education. The analysis of the research instrument was using SPSS series 25 and the all of items being tested were valid with reliability statistic number 896 on Alpha Cronbach scale. The result shown that the child’s education perceiving by the parents falls under the upper-class category with total score 16,341 out of 19,500 perfect score limit.